Current epidemiology of hepatitis E virus infection in the United States: Low seroprevalence in the National Health and Nutrition Evaluation Survey. Issue 3 (17th July 2014) - Ditah, Ivo; Ditah, Fausta; Devaki, Pardha; Ditah, Calistus; Kamath, Patrick S.; Charlton, Michael
<x xml:space="preserve">Abstract</x> Analysis of the National Health and Nutrition Evaluation Survey (NHANES) 1988‐1994 dataset found a relatively high seroprevalence (21%) of hepatitis E virus (HEV) infection in the U.S. general population. Using data obtained within the NHANES 2009‐2010 survey, where a high performance assay for HEV was used, we estimated the weighted seroprevalence of HEV infection among U.S. individuals 6 years and older. We also evaluated factors associated with HEV seropositivity. A total of 8, 814 individuals were included in the analysis. The median age of study participants was 37 years (interquartile range [IQR] 17‐58 years), with 51.2% being female. The weighted national seroprevalence of HEV was 6% (95% confidence interval [CI] 5.1%‐6.9%). About 0.5% of those with HEV had evidence of recent exposure (immunoglobulin M‐positive). In the univariate analyses, factors associated with HEV seropositivity were increasing age (P‐trend < 0.001), birth outside of the U.S., Hispanic race, and "meat" consumption (>10 times/month). No significant association was observed with low socioeconomic status, water source, or level of education. In the multivariate analysis, only older age remained predictive of HEV seropositivity. Conclusion: The weighted national seroprevalence of HEV in the U.S. is much less than previously reported. Using data obtained with a high performance assay, the seroprevalence of HEV was estimated at 6.0% in the U.S. Based on these results, the seroprevalence of HEV is only one‐third as high as previously reported. (Hepatology 2014;60:815–822)